1971
DOI: 10.1111/j.1365-2141.1971.tb02717.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobin, Vitamin B12 and Folate Levels in the Elderly

Abstract: Community-based surveys of a representative sample of 53 3 subjects aged 65 yr and over were conducted in a mining valley and a seaside town in South Wales. Haemoglobin level, PCV, serum vitamin B,, , plasma and red-cell folate were measured and several simple tests of learning and memory were applied. The results give no evidence to suggest that anaemia is common and although low levels of vitamin B,, and folate occurred no evidence of an associated impairment of health was detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 15 publications
4
37
0
Order By: Relevance
“…37 In a Korean population aged 60 to 95 years, the prevalence of anemia was 13.6%, but higher in women (14.7%) than in men (9.9%). 38 In the present study, the prevalence of anemia in the elderly was similar to that found in other population-based studies: 22,23,[39][40][41][42][43][44] 13.2% overall (about 11-12% not considering thalassemia), 12.6% in women and 14.1% in men. The high prevalence of anemia estimated in the very old (over 85 years old, 31.3%) is consistent with that recently reported the Newcastle 85+ cohort for (29.8%).…”
Section: Associations Of Mild Anemia With Other Clinical Conditionssupporting
confidence: 89%
See 1 more Smart Citation
“…37 In a Korean population aged 60 to 95 years, the prevalence of anemia was 13.6%, but higher in women (14.7%) than in men (9.9%). 38 In the present study, the prevalence of anemia in the elderly was similar to that found in other population-based studies: 22,23,[39][40][41][42][43][44] 13.2% overall (about 11-12% not considering thalassemia), 12.6% in women and 14.1% in men. The high prevalence of anemia estimated in the very old (over 85 years old, 31.3%) is consistent with that recently reported the Newcastle 85+ cohort for (29.8%).…”
Section: Associations Of Mild Anemia With Other Clinical Conditionssupporting
confidence: 89%
“…47 Data on mild anemia (hemoglobin concentration between 10.0 g/dL and WHO lower limits of normal) can be drawn only from few, mainly small and not so recent, population-or community-based studies (Online Supplementary Table S3). 17,22,23,[39][40][41][42][43]48 In the present study, mild grade anemia accounted for some 84% of the cases; the majority of these subjects were unaware of being anemic. This seems to confirm that mild anemia in the elderly often goes unscreened and undiagnosed or is disregarded and not reported to the patient by the physician.…”
Section: Associations Of Mild Anemia With Other Clinical Conditionsmentioning
confidence: 93%
“…43 However, the course of subclinical deficiency often appears stationary. [61][62][63] The biochemical abnormalities themselves frequently fluctuate 64,65 ; mildly to moderately elevated MMA levels improved spontaneously in 44% of 432 cases retested 1 to 4 years later, and only 16% worsened. 64 Those observations notwithstanding, the impulse for medical intervention is such that controlled cobalamin trials in subclinical deficiency have been called unethical by some investigators.…”
Section: Expansion and Redefinition Of Cobalamin Deficiencymentioning
confidence: 99%
“…It is reasonable to suppose that the elderly might be particularly prone to develop folic acid deficiency because of diminished financial resources, reduced mobility and apathy over food [8]. Surveys of community-based elderly have found a high prevalence of levels of folate which are below commonly accepted lower limits of the normal range [9] and institutionalised elderly have been found to have significantly low serum and red cell folate levels [10]. Reports have shown low serum folate in 80% of an elderly population [8] and low red cell folate in 70% of a lowincome elderly population [3].…”
Section: Discussionmentioning
confidence: 99%